2015
DOI: 10.1007/s00382-015-2559-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen stable isotope ratios from British oak tree-rings provide a strong and consistent record of past changes in summer rainfall

Abstract: United Kingdom (UK) summers dominated by anti-cyclonic circulation patterns are characterised by clear skies, warm temperatures, low precipitation totals, low air humidity and more enriched oxygen isotope ratios ( 18 O) in precipitation. Such conditions usually result in relatively more positive (enriched) oxygen isotope ratios in tree leaf sugars and ultimately in the tree-ring cellulose formed in that year, the converse being true in cooler, wet summers dominated by westerly air flow and cyclonic conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 57 publications
2
74
0
Order By: Relevance
“…Trends in the isotope data from the modern trees are compared with those in the England and Wales precipitation record for May to August (Alexander & Jones, 2001;Young et al, 2015). Trends in the preindustrial series are compared with relevant sections of a long stable oxygen isotope "master chronology" based on pooled latewood cellulose from 10 separate trees (Loader et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trends in the isotope data from the modern trees are compared with those in the England and Wales precipitation record for May to August (Alexander & Jones, 2001;Young et al, 2015). Trends in the preindustrial series are compared with relevant sections of a long stable oxygen isotope "master chronology" based on pooled latewood cellulose from 10 separate trees (Loader et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Given the cost involved, suitable data sets are sparse and are also heavily biased toward conifers growing at high latitudes and altitudes. No similarly detailed studies have been conducted on European oaks, but the limited evidence that is available suggests that there are no long age trends in oak tree ring δ 18 O (Duffy et al, 2017;Li et al, 2015;Young et al, 2015). However, in perhaps the most comprehensive single study, Young et al (2011) identified no such effect in tree line conifers.…”
Section: 1029/2019gb006195mentioning
confidence: 99%
“…One fate for meteoric water is uptake by plant roots and incorporation into plant tissues; in fact, meteoric water exerts fundamental control on the oxygen isotope signature of plant tissues (Deniro and Epstein, 1979). Because trees are long-lived and tree fossils are abundant in the fossil record, workers have long sought to gain physiological (Gessler et al, 2009;Offermann et al, 2011) or environmental information from the oxygen isotope composition of both modern (Brienen et al, 2012;Knorre et al, 2010;Loader et al, 2010Loader et al, , 2007McCarroll and Loader, 2004;Poussart et al, 2004;Rinne et al, 2013;Saurer et al, 2008;Treydte et al, 2006;Young et al, 2015) and ancient wood (Jahren and Sternberg, 2002, 2008Richter et al, 2008a;Wolfe et al, 2012). Cellulose has been the substrate of choice because it is resistant to degradation (e.g., Griffith et al, 2008;Jahren and Sternberg, 2002) and can be extracted from heterogeneous lignin complexes (Green, 1963 (Csank et al, 2013;Richter et al, 2008b;Saurer et al, 1997;Sternberg et al, 2007;Waterhouse et al, 2002;Yakir and DeNiro, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Loader et al, 2008;Saurer et al, 2008;Young et al, 2012). They can help extend climate reconstructions into regions which are not yet well covered , and also provide information about precipitation amount (Rinne et al, 2013;Young et al, 2015). Recent studies have revealed the sensitivity of cellulose δ 18 O to the combined effects of temperature and humidity, and therefore of drought (Raffalli-Delerce et al, 2004;MassonDelmotte et al, 2005;Etien et al, 2008Etien et al, , 2009Labuhn et al, 2014).…”
Section: Introductionmentioning
confidence: 99%